2015
DOI: 10.1111/ped.12723
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile in two siblings with neonatal lupus erythematosus

Abstract: We studied the cytokine profile of two siblings with neonatal lupus erythematosus (NLE) born to a mother positive for serum anti-Ro and -La antibodies, who did not receive any medication during the two pregnancies. The first sibling was found to have complete atrioventricular block in utero and became severely ill after birth. He fulfilled the diagnostic criteria for hemophagocytic lymphohistiocytosis on day 2. The second sibling did not have any fetal symptoms. He was generally stable after birth, but with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…11 Tanasescu et al 12 demonstrated that LE patients with serum anti-SSA antibodies had more IL-17A-positive lymphocytes in the skin compared to those without anti-SSA antibodies. In addition, Shimozawa et al 13 reported a neonatal LE case, which showed the typical eruptions and elevated serum IL-17. These results suggest a pathogenic association between anti-SSA antibody and IL-17-mediated inflammation in neonatal LE, possibly by Th17 activation via dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Tanasescu et al 12 demonstrated that LE patients with serum anti-SSA antibodies had more IL-17A-positive lymphocytes in the skin compared to those without anti-SSA antibodies. In addition, Shimozawa et al 13 reported a neonatal LE case, which showed the typical eruptions and elevated serum IL-17. These results suggest a pathogenic association between anti-SSA antibody and IL-17-mediated inflammation in neonatal LE, possibly by Th17 activation via dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that LE patients with serum anti‐SSA antibodies had more IL‐17A‐positive lymphocytes in the skin compared to those without anti‐SSA antibodies. In addition, Shimozawa et al 13 . reported a neonatal LE case, which showed the typical eruptions and elevated serum IL‐17.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, 6-65% of patients with HLH have skin involvement during the course of disease [3,5,24]. Also in MAS/HLH, skin findings have been reported [7,25,26]. Cutaneous manifestations of MAS/HLH are however aspecific as most patients present with a transient generalized maculopapular eruption.…”
Section: Skin Lesionsmentioning
confidence: 99%
“…It has rarely been associated with neonatal lupus. So far, only four patients have been reported in the literature (Table 1) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found increased frequencies of IFNγ‐producing cells (both NK and T cells) in cord blood from neonates exposed to anti‐Ro/La antibodies, 83 suggesting that a general activation of innate immune mechanisms may not be restricted to autoimmune CHB cases. In fact, hypercytokinemia has been reported, not only in a few cases of autoimmune CHB or non‐cardiac NLE, 87 but also in babies born to mothers with other systemic rheumatic diseases 69 . An interesting hypothesis is that foetuses exposed to maternal anti‐Ro/La antibodies and/or type I IFN have an activated, pro‐inflammatory immune profile that facilitates the development of CHB manifestations brought about by additional events and/or susceptibility factors.…”
Section: Time To Look Beyond Macrophage‐driven Inflammation and Fibromentioning
confidence: 99%